High-resolution nuclear magnetic resonance spectroscopy in microfluidic droplets. Issue 19 (22nd August 2018) - Hale, William; Rossetto, Gabriel; Greenhalgh, Rachael; Finch, Graeme; Utz, Marcel
Abstract : Combining structural shimming with paramagnetic doping removes magnetic susceptibility mismatches, allowing meaningful NMR spectroscopy of microfluidic droplet emulsions. Abstract : A generic approach is presented that allows high-resolution NMR spectroscopy of water/oil droplet emulsions in microfluidic devices. Microfluidic NMR spectroscopy has recently made significant advances due to the design of micro-detector systems and their successful integration with microfluidic devices. Obtaining NMR spectra of droplet suspensions, however, is complicated by the inevitable differences in magnetic susceptibility between the chip material, the continuous phase, and the droplet phases. This leads to broadening of the NMR resonance lines and results in loss of spectral resolution. We have mitigated the susceptibility difference between the continuous (oil) phase and the chip material by incorporating appropriately designed air-filled structures into the chip. The susceptibilities of the continuous and droplet (aqueous) phases have been matched by doping the droplet phase with a Eu 3+ complex. Our results demonstrate that this leads to a proton line width in the droplet phase of about 3 Hz, enabling high-resolution NMR techniques.